PENGGUNAAN MODEL CONCEPTUAL CHANGE PADA INSTRUMEN THREE-TIER-TEST DAN LKPD - Dwi Anggraeni Riswana; Rusmini Rusmini (Orbital: Jurnal Pendidikan Kimia, 2020)
There are still many misconceptions in the buffer solution material based on the results of pre-research that has been done. Therefore, it is necessary to to make efforts to reduce misconceptions. This research aims to determine the validity of the three-tier-test diagnostic test instrument and Student Worksheet (LKPD) to reduce student’s misconceptions through conceptual change model on buffer material. This research and development method uses a 3-D model which is a modification of the 4-D model, namely (1) define; (2) design; and (3) development. The validity of the instrument and LKPD in terms of content validity and construct validity. The content validity of the instruments and LKPD respectively obtained an average percentage of 94.00% and 92.44%. While the construct validity of the instruments and LKPD respectively obtained an average percentage of 91.00% and 86.47%. This results shows that the three-tier-test diagnostic test instrument and LKPD through conceptual change model developed were declared very valid.